(untitled) (INNOVATIVE ECONOMY, 2026)
Yadchyshyn O.V. MECHANISMS FOR STIMULATING THE CIRCULAR ECONOMY IN THE CONDITIONS OF POST-WAR RECONSTRUCTION OF UKRAINE Purpose. The aim of the article is to substantiate the mechanisms for stimulating the circular economy in the conditions of post-war reconstruction of Ukraine, to define their multi-level architecture, and to propose an applied approach to the implementation of circular solutions at the state level, the level of territorial communities, and the level of enterprises. Methodology of research. A set of general scientific and special methods was used, in particular: methods of analysis and synthesis – to generalize modern scientific approaches to understanding the circular economy and mechanisms for its stimulation; systematization – to structure stimulation mechanisms by levels of implementation and functional purpose; logical and structural method – to build a table for the implementation of circular solutions in the post-war reconstruction system; analytical generalization – to form practical conclusions on the adaptation of relevant mechanisms to Ukrainian conditions. Findings. The article establishes that in the conditions of post-war reconstruction, the circular economy should be considered not as a narrowly ecological concept, but as an applied mechanism for resource conservation, reducing the material intensity of reconstruction and increasing the economic sustainability of territories. It was found that the key barriers to its development in Ukraine remain the fragmentation of institutional regulation, weak economic incentives, underdevelopment of the recycling infrastructure, insufficient integration of circular requirements into recovery programs, and uneven capacity of territorial communities to manage local resource flows. The feasibility of dividing incentive mechanisms into four interconnected blocks is substantiated: regulatory and economic framework, procurement mechanisms, investment instruments, and local incentives for communities and business. A table for implementing circular economy incentive mechanisms is proposed, within which standardization and financial incentives are prioritized at the state level, inventory of resource flows, circular procurement, and territorial coordination at the community level, and resource-locked business models, material flow audits, and partnerships with local market participants are prioritized at the enterprise level. It is proven that only the coordinated functioning of these levels creates the prerequisites for the transition from fragmented environmental practices to a systemic model of circular recovery. Originality. The approach to substantiating mechanisms for stimulating the circular economy in the conditions of post-war recovery through a combination of institutional, territorial and entrepreneurial levels of implementation has been further developed. Unlike existing approaches, the proposed approach connects state policy instruments, administrative actions of territorial communities and business decisions of enterprises within a single logic of reconstruction. Practical value. The proposed provisions can be used in the development of state and regional programs for post-war recovery, the formation of a policy to support resource-efficient production, the improvement of the public procurement system, the planning of local infrastructure for processing and reuse of materials, as well as in the activities of enterprises that integrate circular models into their own business processes. Key words: state regulation, territorial communities, circular procurement, reuse, recycling, sustainable development, local resource flows, institutional support.